Triterpenes from Vitex limonifolia. - Kim Thoa, Nguyen Thi; Ban, Ninh Khac; Trang, Do Thi; Linh, Tran My; Giang, Vu Huong; Nhiem, Nguyen Xuan; Kiem, Phan Van (Vietnam Journal of Chemistry, 2017)
Using combined chromatographic methods, four triterpenoids, 2α,3α-dihydroxyurs-12-en-28-oic acid (1), euscaphic acid (2), 2α,3α-dihydroxy-19-oxo-18,19-seco-urs-11,13(18)-dien-28-oic acid (3), and maslinic acid (4) were isolated from the methanol extract of the leaves of Vitex limonifolia. Their structures were elucidated by 1D-, 2D-NMR spectra as well as by comparison with those reported in the literature. Compound 3 was reported from Vitex genus for the first time. Keywords. Vitex limonifolia, triterpenoid, ursane, oleanane.